Community Forestry in Nepal: Achievements and Challenges - Kanel, Keshav (Journal of Forest and Livelihood, 2004)
Community forestry program in Nepal officially started in late 1970s. Since then concerning movement has been evolving to involve local communities in the management and utilization of forests. The policy of the government was originally intended to meet the basic forest products required by the communities through active participation in forest development and management. Later, it was expanded to include the mobilization and empowerment of the members of community forest user groups in the development of their local communities. It is observed that the trend of forest degradation has decreased since the handing over of national forests to local communities, but a number of unintended social anomalies have also cropped up. Such anomalies essentially constitute of the inequity and unfairness in the local and national level and in terms of long-term sustainability of forest resources. This paper provides an overview of various issues of community forestry, especially focusing on the major achievements made in community forestry. It calls for rethinking community forestry program in order to face the present day challenges of linking community forestry with livelihood promotion, good governance, and sustainable forest management. It also lays out strategy for reforms in community forestry.